THE GLORY OF THE MOTHERLAND IN THE WORK OF ZAHIDDIN MUKHAMMAD BABUR - Хужамова Намунахон Халиджановна (American Journals, 2023)
This article tells about the life and creativity of the great commander and poet Zahiriddin Muhammad Mirzo Babur and talks about the feeling of love for the motherland,the homesickness and glorification of the motherland in his work.
Keywords: Baburnoma, Murran, Movarounnahr, Ghazna, Kabul, India, Ghazal, Vatan, ruboi, chicken, poetry.